Prediction of obstetric complications in women with hypertensive disorders of pregnancy - Vaskiv, O.V.; Horbatiuk, O.H.; Hryhorenko, A.P.; Harbuziuk, V.V.; Zhylko, O.L.; Perebendiuk, T.V. (Medicni Perspektivi, 2025)
In the structure of maternal mortality causes, hypertensive disorders of pregnant women rank third. Hypertensive disorders of pregnant women can cause abortion and premature birth, fetal growth retardation, fetal hypotrophy, fetal hypoxia, premature detachment of a normally located placenta, and even fetal death. The aim of the study is to develop a mathematical model for predicting the risk of obstetric complications in women with gestational hypertensive disorders. Determination of independent predictors of obstetric complications of pregnancy and creation of a mathematical model for predicting the risk of obstetric complications in women with hypertensive disorders of pregnancy was performed using multiple stepwise linear regression analysis. Statistical analysis of the data was carried out according to standard methods using the «STATISTICA 5.5». In order to develop a mathematical model for predicting obstetric complications of pregnancy from the point of view of the influence of hypertensive disorders of pregnancy, data from a retrospective analysis of 60 women with hypertensive disorders of pregnancy were included in the multivariate statistical analysis. Women who had adverse obstetric outcomes of pregnancy (n=15) formed the main group (1-М). The group of women without complications of pregnancy and childbirth consisted of 45 people and was defined as a control group (1-C). The most significant independent predictors of obstetric complications of gestation in pregnant women with hypertensive disorders were identified, namely: systolic blood pressure, risk of preterm birth, primary manifestation of hypertensive abnormalities at 31-32 weeks of pregnancy, endothelin-1 concept in blood plasma and umbilical cord artery pulsatility index. It was found that the value of the multiple regression equation of the proposed model ≥503.38 points makes it possible to predict adverse obstetric outcomes of pregnancy in women with gestational hypertensive disorders in this pregnancy with a sensitivity of 73.3% and a specificity of 68.9%. Thus, the prognostic model developed by us with a fairly high sensitivity and specificity allows predicting obstetric outcomes of pregnancy in women with hypertensive disorders of pregnancy.